Capturing 50 Years of Postseismic Mantle Flow at Nankai Subduction Zone. Issue 11 (8th November 2018) - Johnson, Kaj M.; Tebo, Douglas
Abstract: We combine Global Positioning System, leveling, and tide gauge records of vertical motion in southwest Japan spanning postseismic deformation following the 1944 M8.1 Tonankai and 1946 M8.4 Nankai earthquakes. Continuous tide gauge records from 1950 to 2015 are combined with leveling data recorded from 1947 to 1980 and Global Positioning System data beginning in 2003 to estimate the spatiotemporal evolution of the vertical velocity field. The combined field shows postseismic subsidence centered approximately 250 km inland from the trench that steadily decreases in rate from 1947 until about 1995. Postseismic uplift is observed in a 50‐km‐wide belt along the southeast coastline that rapidly decays and reverses to subsidence by the mid‐1960s. Both afterslip and viscoelastic mantle flow mechanisms are required to explain the 50‐year postseismic deformation transient. We develop a 2‐D postseismic deformation model consisting of a linear Maxwell viscoelastic mantle and an elastic subducting slab and overriding plate. Rate‐strengthening afterslip on the subduction interface between 20‐ and 45‐km depth and viscoelastic mantle flow relax imposed coseismic stress. Mantle flow with material relaxation time of 8–15 years (viscosity of order 10 19  Pa s) is required to fit the data. The inland postseismic subsidence signal is diagnostic of postseismic flow in the mantle wedge. Models with rate‐strengthening afterslip in an elastic half‐space without mantle flow do not produce inland subsidence. The coastal postseismic uplift is largely driven by afterslip. We conclude that vertical deformation data in southwest Japan unambiguously capture 50 years of postseismic mantle flow. Key Points: Tide gauge records, leveling data, and GPS‐derived velocities are combined to form a postseismic vertical deformation field from 1947 to 2015 in southwest Japan Two‐dimensional models show that afterslip and mantle flow mechanisms are required to explain the postseismic transient Vertical deformation data in southwest Japan unambiguously capture 50 years of postseismic mantle flow